2017
DOI: 10.1111/vru.12527
|View full text |Cite
|
Sign up to set email alerts
|

Imaging characteristics and treatment of a penetrating brain injury caused by an oropharyngeal foreign body in a dog

Abstract: A 4-year-old Border collie was presented with one episode of collapse, altered mentation, and a suspected pharyngeal stick injury. Magnetic resonance imaging (MRI) and computed tomography showed a linear foreign body penetrating the right oropharynx, through the foramen ovale and the brain parenchyma. The foreign body was surgically removed and medical treatment initiated. Complete resolution of clinical signs was noted at recheck 8 weeks later. Repeat MRI showed chronic secondary changes in the brain parenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
0
16
1
Order By: Relevance
“…The following case report describes the presence of an intracranial sewing needle secondary to the needle ingestion. To the author’s knowledge, this is the first veterinary report of an intracranial sewing needle and the second report of an intracranial foreign body secondary to pharyngeal perforation 9…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The following case report describes the presence of an intracranial sewing needle secondary to the needle ingestion. To the author’s knowledge, this is the first veterinary report of an intracranial sewing needle and the second report of an intracranial foreign body secondary to pharyngeal perforation 9…”
Section: Introductionmentioning
confidence: 84%
“…Indeed, the pharyngeal anatomical and physiological barriers do not always permit deglutition of the needle, leading to persistence of this sharp foreign body into the pharynx 8. However, one clinical case described intracranial perforation secondary to wood stick ingestion in a dog, highlighting the possibility of a pharyngeal foreign body progressing into the cranial cavity 9…”
Section: Introductionmentioning
confidence: 99%
“…Within the veterinary literature, few papers describe intracranial migration of foreign material through obscure routes (Dennis et al 2005, Lazzerini et al 2016. McKenzie et al (2019) and Sauvé et al (2012), identified a wooden cocktail stick and a porcupine quill crossing the foramen ovale; Caraty et al (2020) detected a needle perforating the caudal cranial fossa. In our case, we identified the entrance route as the foramen lacerum.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, intracranial foreign bodies have been described as a consequence of perforations through the oral cavity, the nasal cavity and the orbits (Daoust 1991, Dennis et al 2005, Sauvé et al 2012, Lazzerini et al 2016, McKenzie et al 2019, Caraty et al 2020. This case report describes a sewing needle swallowed by a dog that passed into the right neurocranium through the right foramen lacerum.…”
Section: Introductionmentioning
confidence: 97%
“…Penetrating brain injuries are uncommon in veterinary medicine, with only a few cases reported in the literature (Burgisser & Hintermann, 1967;Cottam & Gannon, 2015;Daoust, 1991;McCandlish & Ormerod, 1978;McKenzie et al, 2019;Park et al, 2010;Sauvé et al, 2012). Many of these reports involve foreign body penetration of the nasal cavity, nasopharynx, oropharynx, and foramen magnum and only one report involves penetration of the orbit.…”
Section: Introductionmentioning
confidence: 99%